Variables predictors of the set in the defence complex in volleyball - González-Silva, J.; Moreno, A.; Fernández-Echeverria, C.; Claver, F.; Moreno, M. P. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2018)
The objective of the research was to analyse the variables predictors of the setting efficacy in the defence complex (KII), in youth athlete, in both genders. The study sample was comprised of 2404 game actions, 1104 in the male gender and 1300 in the female gender. The actions were carried out by the 34 teams that participated in the Spanish Under-16 Championship. The dependant variable was the setting efficacy. The results determined that, in both genders, the dig efficacy, setting technique and the participation in block predicted the setting efficacy; in male gender, the defence zone and tempo of set; no predictor variables were exclusive to the female gender. This information may be relevant when developing training processes in volleyball.